let G be a group. Let a,b an element of G . Prove that G is abelian iff  (ab)^-1 = a^-1b^-1.

Asked on by aclawrence

1 Answer | Add Yours

embizze's profile pic

embizze | High School Teacher | (Level 2) Educator Emeritus

Posted on

A group is abelian if the operation has the commutative property, i.e. ab=ba for all a,b in the group.

(1) `(ab)^(-1)=a^(-1)b^(-1)=>ab=ba`

`` `(ab)^(-1)=a^(-1)b^(-1)`







`ab=ba` by the symmetric property.`quad`

(2) `ab=ba==>(ab)^(-1)=a^(-1)b^(-1)`









as required.

We’ve answered 319,814 questions. We can answer yours, too.

Ask a question